205k views
4 votes
7x+3y=7/6
Y=6x-1
Use the method of substitution to solve

User Achie
by
5.0k points

2 Answers

3 votes

Answer:

x= 1/6

y= 0

Explanation:

7x+3(6x-1) = 7/6 Substitute in.

7x+18x-3 = 7/6 Distributive Property.

25x = 25/6 Isolate the variable.

x= 1/6 Divide by 25.

y= 6(1/6)-1 Substitute in.

y= 1-1 Multiply.

y= 0 Subtract.

User Fnery
by
5.9k points
2 votes

Answer:

X=1/6 Y=0

Explanation:

If Y= 6x-1, substitute Y on the first equation

7x+3(6x-1)=7/6

7x+18x-3=7/6

25x=(7/6)+3

25x=25/6

x=1/6

Then substitute X on the second equation

Y=6(1/6)-1

Y=0

User Nidhi
by
5.1k points